Thieves of state [why corruption threatens global security] - Chayes, Sarah (Prince Frederick, MD : Recorded Books, 2015)
A former advisor to the Joint Chiefs of Staff explains the role played by acute government corruption in fostering violent extremism.
Subtitle from container.
Compact discs.
In container (16 x 18 cm.).
"With tracks every 3 minutes for easy book marking"--Container.
Narrated by the author.
Keywords: Political corruption -- Case studies; Security, International -- Case studies; Political corruption; Security, International; Audiobooks; Case studies